Association of Helicobacter pylori infection with esophageal adenocarcinoma and squamous cell carcinoma: a meta‐analysis. Issue 7 (17th March 2014) - Nie, S.; Chen, T.; Yang, X.; Huai, P.; Lu, M.
Summary To evaluate the relationship of Helicobacter pylori and cytotoxin‐associated gene A (CagA) positive strains with esophageal neoplasm, including esophageal adenocarcinoma (EAC) and esophageal squamous cell carcinoma (ESCC), the authors conducted a meta‐analysis using a predefined protocol. PubMed, Web of Science, China biology medical literature database, Wanfang, and China National Knowledge Infrastructure were searched for relevant articles from the first available year to April 8, 2013. The fixed or random effect pooled measure was selected based on heterogeneity among studies, which was evaluated using Q test and the I2 of Higgins and Thompson. Metaregression was used to explore the sources of between‐study heterogeneity. Publication bias was analyzed by Begg's funnel plot and Egger's regression test. The association was assessed by odds ratio (OR) with 95% confidence interval (CI). A total of 28 eligible studies were included in the meta‐analysis. There was a significant inverse association between H. pylori infection (pooled OR, 0.57; 95% CI, 0.44–0.73) and EAC; CagA‐positive H. pylori strains were less likely to be associated with EAC compared with CagA‐negative strains (pooled OR, 0.64; 95% CI, 0.52–0.79). However, there was no statistically significant association between H. pylori/CagA‐positive H. pylori strains infection and ESCC, and the pooled ORs were 1.16 (95% CI, 0.83–1.60) and 0.97 (95% CI, 0.79–1.19). But significant associations between CagA‐positive H. pylori strains infection and ESCC risk were found in the stratified analysis of the study location (Asian and non‐Asian), and the summary ORs were 0.74 (95% CI, 0.57–0.97) and 1.41 (95% CI, 1.02–1.94). H. pylori infection and CagA‐positive strains are associated with decreased risk of EAC in the overall population. No significant association was found between H. pylori infection/CagA‐positive strains and ESCC. But CagA‐positive strains might have a positive association with ESCC in non‐Asian population and an inverse association in Asian population.